2006
DOI: 10.3892/ijo.28.1.209
|View full text |Cite
|
Sign up to set email alerts
|

HPV-16 E6 oncoprotein impairs the fidelity of DNA end-joining via p53-dependent and -independent pathways

Abstract: Abstract. We previously reported that the E6 oncoprotein of high-risk human papillomavirus (HPV) caused genetic instability and oncogenesis by disrupting cellular DNA repair. Here, to investigate the effect of different domains of E6 on DNA double-strand break (DSB) repair, we infected normal human oral fibroblasts (NHOF) with retroviruses expressing wild-type (wt) or mutant (mt) HPV-16 E6 and examined the cellular DNA end-joining (EJ) activity. The cells expressing E6 showed not only a diminution of errorfree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 33 publications
1
34
0
2
Order By: Relevance
“…RNA (1 µg) was reverse transcribed using SuperScript II TM RNase H reverse transcriptase and oligo (dT) [12][13][14][15][16][17][18] (Invitrogen Ltd) following the manufacturer's guidelines. The Human Universal ProbeLibrary Set (Roche, West Sussex, UK) employing proprietary locked nucleic acid analogues was used for real-time quantitative PCR to measure expression levels in genes of interest.…”
Section: Real-time Quantitative Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA (1 µg) was reverse transcribed using SuperScript II TM RNase H reverse transcriptase and oligo (dT) [12][13][14][15][16][17][18] (Invitrogen Ltd) following the manufacturer's guidelines. The Human Universal ProbeLibrary Set (Roche, West Sussex, UK) employing proprietary locked nucleic acid analogues was used for real-time quantitative PCR to measure expression levels in genes of interest.…”
Section: Real-time Quantitative Pcrmentioning
confidence: 99%
“…However, HPV hijacks the host DNA polymerase; therefore, the effect of cidofovir is not related to polymerase specificity as it is for CMV. Thus, the response of HPV-infected cells to cidofovir is probably related to the established ability of this virus to negatively influence the DNA repair capacity of cells [13,14]. These studies describe the effects of high-risk HPV on DNA repair processes, yet it is known that low-risk virus can also compromise the function of p53, albeit not to the same extent as high-risk virus [15].…”
Section: Introductionmentioning
confidence: 99%
“…E6 interferes with the ssDNA repair protein XRCC1 (Iftner et al 2002). Both oncoproteins influence the ATR downstream effector kinase Chk1; E6 deregulates the kinase, preventing NHEJ and recovery of stalled replication forks in a p53-independent manner (Shin et al 2006a, Chen et al 2009), while E7 is known to induce degradation of claspin, a regulator of Chk1 (Spardy et al 2009, Jiang andImperiale 2012). The E6 proteins of cutaneous HPVs such as HPV 5 and 8 are reported to abrogate both ATM and ATR pathways (Wallace et al 2012(Wallace et al , 2013.…”
Section: E6 and E7mentioning
confidence: 99%
“…High-risk HPV E6 is believed to interfere with end joining in a p53-dependent manner (Shin et al 2006a), which could affect genomic stability as NHEJ increases the risk of HPV genome integration. Additionally, genetic variations in the repair proteins XRCC4 and Mre11A considerably increase the risk of HPV18 genome integration and possible tumorigenesis (Amirian et al 2012, Anacker et al 2014, Moody and Laimins 2009.…”
Section: Ddr Homologous Recombination and Pv Replicationmentioning
confidence: 99%
“…This protein plays an important role in p53-dependent response to DNA damage and oxidative stress [Lembo et al, 2006]. E6 expression has also been involved in the presence of defective global and transcription-coupled NER (GNER and TCNER, respectively), in reduced repair of UV-induced thymine dimers, in impaired doublestrand break repair, and in the degradation of the O 6 -methylguanine-DNA methyltransferase that removes alkyl groups from guanine [Therrien et al, 1999;Srivenugopal and Ali-Osman, 2002;Giampieri and Storey, 2004;Shin et al, 2006]. Finally, it has been observed that E7-expressing fibroblasts are deficient in GNER [Therrien et al, 1999].…”
Section: Hpv Oncogenes and Dna Damage Responsementioning
confidence: 99%